Analysis of the Influence of Electronic Word of Mouth (E-WOM) on Social Networking Sites (SNS) on Online Purchase Intention on iPhone Smartphones - Muhammad Farhan; Anas Hidayat (Cita konsultindo, 2024)
Electronic word-of-mouth (eWOM) on social networking sites (SNS) has become crucial in shaping consumers’ online purchase intentions, reflecting the increasing reliance on the wealth of user-generated content and recommendations shared on these platforms. This study aims to investigate the relationships between eWOM information factors, including information usefulness, information adoption, attitude toward information, and their impact on online purchase intentions. This study uses a quantitative approach, utilizing a questionnaire to collect data from 340 individuals who actively engage in eWOM activities on various SNS platforms. Statistical analysis was conducted using partial least squares structural equality modelling (PLS-SEM). The findings indicate that information usefulness has a positive and significant effect on attitude toward information, information usefulness has a positive and significant effect on online purchased intention, attitude toward information has a positive and significant effect on online purchased intention, attitude toward information has a positive and significant effect on information adoption, and information adoption has a positive and significant effect on online purchased intention. This suggests that consumers may have a favourable view of eWOM content and actively adopt it. Information adoption emerges as an important determinant of online purchase intention, emphasizing the importance of promoting user engagement and trust in eWOM information. These findings contribute to a deeper understanding of online consumer behaviour and provide valuable guidance for stakeholders who wish to leverage eWOM effectively in digital marketing.